Enhance Security of the Field Flight Polytechnic Network and the Speed of the Internet Gateway in Virtual Box - M. Amril Siregar; Indah Vusvitasari; Ivana Wardani (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The development of information technology (IT) is currently growing rapidly, many from the lower middle class to businessmen and even entrepreneurs need internet network access. An internet network is a form of communication between computer networks around the world, wherewith the internet each computer located at a distance can communicate with each other, exchange information and resources. Currently, many networks are built using different network devices, one of which is a router. A router is a device for sending data packets between networks through a process called routing. In the market, many companies produce routers, one of which is Mikrotik with its product in the form of Mikrotik RouterOS which has been widely used to handle existing networks. So far, Mikrotik configuration has been a problem for some people because of ignorance in managing the network used so that many errors and fraud occur on the network used, even though products from Mikrotik have configuration programs based on GUI (Graphical User Interface) but still require long and confusing steps even if only to do configurations such as internet gateways.